Biological pre-treatment of banana pseudo stem with white rot fungi and its effects on pulp and paper properties - Razali, Norhaslida (2015)
Wood fibre is known to be a major raw material for most paper industries all over the world. However, a great concern in forest resources conservation calls for an overall plan for utilization of non-woody plants. This study was carried out using banana pseudo stem (Musa acuminata var. truncata) as potential raw material for pulp and paper. In paper production, chemicals disposal process requires high cost and causes negative effects to the environment. Biopulping has showed potential in providing environmentally-friendly technology for pulp and paper production. This research was aimed at investigating the effect of fungi pre-treatment in lignin removal prior to the pulping process and their effect to the pulp and paper properties. Research studies have been geared toward properties of banana pseudo stem, fungi pre-treatment on banana pseudo stem, optimisation of soda pulping process and biosoda pulping process. Properties of banana pseudo stem include botanical aspects, anatomical structures, fibre morphology and chemical compositions. From the anatomical observation, it showed that banana pseudo stem consists of fibre bundle, vascular bundle and lots of parenchymatous cells. Banana pseudo stem fibres were discovered to have long fibre which range from 3.34 mm to 4.19 mm and had lower runkel ratio, high coefficient of suppleness and higher felting power. Chemical composition of banana pseudo stem consisted of more holocellulose (71.68%), alpha-cellulose (68.30%) and remarkable lower lignin content (14.34%). Fungal pre-treatment study was carried out to determine the best fungus species and a suitable pre-treatment period to be used in biosoda pulping. The pre-treatment was done using banana chips that were inoculated with Pycnoporus sanguineus and Oxyporus latemarginatus in 5, 10 and 15 days incubations. P. sanguineus appeared to grow much faster compared to O. latemarginatus on banana chips and gave the highest weight loss (29.36%). P. sanguineus secreted sole ligninolytic enzyme Laccase with the highest level of activity which was 6.07 U/ml in 15 days and showed preference to degrade mainly on lignin (24.85% reduction) with minimal loss of holocellulose and alpha-cellulose. O. latemarginatus was found to secrete lignin peroxidase and manganese peroxidase and appeared to degrade more on lignin (18.92%) and cellulose (45.93%). Soda pulping process was carried out at different cooking time (30 and 60 mins) and different alkali percentage (10, 12, 14 and 16%). It was found that a combination of 30 mins cooking time and 14% alkali produced higher pulp yield (40.91%) and also gave better result in pulp and paper properties. Biosoda pulping was carried out using. P. sanguineus with the incubation period of 15 days. Pulp and paper properties of soda pulping and biosoda pulping were compared. Biosoda pulping appeared to give the highest pulp yield with 47.57% and also better in tensile index, burst index, and tear index and also brightness. Scanning Electron Microscope (SEM) observation of treated handsheets indicated that there were less voids between fibres, and the fibres collapsed onto each other which contributed to good bonding. From the research, the fungal pre-treatment prior to pulping process helped to improve pulp and paper properties.